Improvement in oxidation behaviour of steel by B4C–TiB2–TiC–Ni coating. (November 2014) - Rafiei, M.; Shamanian, M.; Salehi, M.; Motallebzadeh, A.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, B4C–TiB2–TiC–Ni coating was thermally sprayed on the surface of 4130 steel substrate by high velocity oxyfuel (HVOF) torch. Before the HVOF process, the B4C–TiB2–TiC–Ni powder was prepared by mechanical alloying (MA). In order to study the oxidation behaviour of the coating and 4130 steel, thermogravimetric analysis (TGA) was done. The structural evolution of the samples was investigated by X-ray diffractometry (XRD). The microstructure and elemental analysis of the samples were studied by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The coating showed higher oxidation resistance in comparison with the 4130 steel at high temperatures. It was also found that the dissolution of oxygen in the coating was the rate determining process of the coating oxidation, creating the quasi-cubic kinetic rate.